Palladium-Catalyzed Asymmetric α-Arylation of Alkylnitriles - Jiao, Zhiwei (2017)
Asymmetric arylation of alkylnitriles forms quaternary stereocenters in good enantiocontrol for the first time. A lithium heterodimer consisting of an alkylnitrile anion and a disilylamide ion is the actual species responsible for the stereodetermining transmetalation in the catalytic cycle.